Enhancing physical fitness in elite field hockey players with a twelve-week functional training program: a cluster randomized control trial - Bashir, Marrium; Hucheng, Ma; Geok, Soh Kim; Akbar, Saddam; Zhang, Dong (Bursa Uludag Universitesi, 2024)
This study aimed to explore the impact of functional training on the physical fitness of young elite field hockey players. The study comprised 40 young elite male field hockey players with the following characteristics (mean ± SD age: 21.5 ± 0.8 years; height: 176.9 ± 2.6 cm; weight: 68.4 ± 5.1 kg; BMI: 21.8 ± 1.3; training experience: 51.2 ± 5.4 months). Twenty participants were allo-cated to two groups: the functional training group (FTG) and the control training group (CG). Each group received 60-minute training sessions three times per week for 12 weeks. Generalized estimating equation analysis and a Bonferroni test for pairwise comparisons were used to assess the intervention's efficacy. Before the start of the exercise program, no statistically significant differences were observed in physical fitness measures between the FTG and CG (p > 0.05). However, by the sixth week, a significant difference appeared in both the T-Agility test (p < 0.001) and endurance (p = 0.024) between the two groups, while no notable distinctions were detected in other fitness parameters (p > 0.05). After a 12-week training program, the FTG demonstrated improvements in all physical fitness measures [flexibility (p < 0.001); Illinois agility test (p < 0.001); T-agility test (p = 0.020); endurance (p < 0.001)] except speed, which exhibited no significant impact (p = 0.175). Notable enhancements in T-agility and endurance were evident after just six weeks of functional training, and a 12-week functional training regimen showed superiority over standard training approaches in young elite male field hockey players. These findings encourage the efficacy of functional training exercises over traditional methods in enhancing athletes' fitness parameters.